Improving The Learning Outcomes of Class VII Students in The Use of Audio Visuals on The Material "Avoiding Gibah and Carrying Out Tabayyun" at SMPN 1 Rao Sub-District - Mutiah (BiCED Proceeding, 2024)
This study aims to evaluate the effectiveness of using audiovisual media in the teaching of Islamic Religious Education (PAI) at SMPN 1 Rao. The research was conducted through a descriptive approach with Classroom Action Research (CAR) as the type, involving two cycles. In the first cycle, the use of audiovisual media successfully increased student participation and showed an improvement in learning outcomes, with an average class score of 74. However, the involvement of some students remained limited. In the second cycle, the use of more interactive and varied audiovisual media increased student participation to 90%, with the average class score reaching 82. The results of the study indicate that the proper use of audiovisual media can enhance student learning outcomes and provide a more engaging and meaningful learning experience.